2020
DOI: 10.1016/j.jaci.2019.06.049
|View full text |Cite|
|
Sign up to set email alerts
|

Next-generation Allergic Rhinitis and Its Impact on Asthma (ARIA) guidelines for allergic rhinitis based on Grading of Recommendations Assessment, Development and Evaluation (GRADE) and real-world evidence

Abstract: Selection of pharmacotherapy for patients with allergic rhinitis aims to control the disease and depends on (1) patient empowerment, preferences, and age; (2) prominent symptoms, symptom severity, and multimorbidity; (3) efficacy and safety of treatment 1 ; (4) speed of onset of action of treatment; (5) current treatment; (6) historic response to treatment; (7) effect on sleep and work productivity 2,3 ; (8) self-management strategies; and (9) resource use. 4,5 An algorithm was devised 5 and digitalized 6 to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
246
0
37

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 362 publications
(314 citation statements)
references
References 66 publications
2
246
0
37
Order By: Relevance
“…10 Additionally, being the hospitals active only for urgency/emergencies, we cannot exclude the exacerbation of other preexisting comorbidities or the onset of new ones. Unfortunately the restrictions imposed by the lockdown, although necessary to fight the pandemic, were not in accordance with the indications suggested by the ARIA (Allergic Rhinitis and its Impact on Asthma) guidelines, 11,12 according to which avoiding contact with the allergen in both indoor and outdoor environments is the most effective primary preventive measure in patients with respiratory allergies. When this is not possible as at present, a "perfect storm" occurs and the role of "counseling" through phone calls and telehealth is crucial.…”
mentioning
confidence: 99%
“…10 Additionally, being the hospitals active only for urgency/emergencies, we cannot exclude the exacerbation of other preexisting comorbidities or the onset of new ones. Unfortunately the restrictions imposed by the lockdown, although necessary to fight the pandemic, were not in accordance with the indications suggested by the ARIA (Allergic Rhinitis and its Impact on Asthma) guidelines, 11,12 according to which avoiding contact with the allergen in both indoor and outdoor environments is the most effective primary preventive measure in patients with respiratory allergies. When this is not possible as at present, a "perfect storm" occurs and the role of "counseling" through phone calls and telehealth is crucial.…”
mentioning
confidence: 99%
“…Of note, randomized clinical trials showed that xed-dose formulation is more effective than loose combinations of corticosteroids and antihistamines in patients with moderate/severe seasonal AR (44). The newest ARIA guidelines based on both Grading of Recommendations Assessment, Development and Evaluation (GRADE) and real-world evidence (RWE) con rm and emphasize e cacy of xed-dose combination of intranasal Aze/ u for both nasal and ocular symptom relief and recommend the use of this drug as rst line therapy for AR patients (45). Our analysis showed that xed-dose combination intranasal Aze/ u was used in both monotherapy and polytherapy regimens, with signi cant differences across clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, randomized clinical trials showed that xed-dose formulation is more effective than loose combinations of corticosteroids and antihistamines in patients with moderate/severe seasonal AR (44). The newest ARIA guidelines based on both Grading of Recommendations Assessment, Development and Evaluation (GRADE) and real-world evidence (RWE) con rm and emphasize e cacy of xed-dose combination of intranasal Aze/ u for both nasal and ocular symptom relief, adding this drug to rst line therapies for AR patients (45). Of interest, our analysis showed that xed-dose combination intranasal Aze/ u was used in both monotherapy and polytherapy regimens, with signi cant differences across clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many researchers reported that dissatisfaction with treatment may cause non-adherence to therapy (51)(52)(53), whereas more recent studies revealed that patients discontinue their treatment when they felt better (47,54). In contrast to guidelines recommending the use of multiple drugs to achieve symptom control (45), recent data indicated that most patients experience poor symptom control with increasing medications (26,55). Hence, the use of single drug-based therapy could substantially ameliorate patient compliance.…”
Section: Discussionmentioning
confidence: 99%